A Case of Previously Unsuspected Cardiac Sarcoidosis Diagnosed at Autopsy and 23-Year Review of One Institution's Sarcoidosis Deaths. Issue 1 (March 2019) - Miller, Catherine R.; Boor, Paul J.; Campbell, Gerald A.
Sarcoidosis is a noncaseating granulomatous disease of unknown etiology. The incidence is 11 per 100 000 white individuals and 34 per 100 000 black individuals. Cardiac involvement is seen in 2% to 5% of patients with systemic sarcoidosis and is often clinically undetected. This may be due to relative rarity of cardiac involvement, variability in presentation, or that there are no good clinical criteria for the diagnosis of cardiac sarcoidosis. Patients may be totally asymptomatic or have heart block, myocardial infarctions, heart failure, or sudden cardiac death, which may be due to involvement of the conduction system by sarcoidosis. We present a case of a 54-year-old black male with hypertension and hyperlipidemia. Prior to his death, he was witnessed to suddenly stand up, grab his chest, and collapse. His clinical cause of death was hypertensive and atherosclerotic cardiovascular disease. A retrospective review of autopsy cases over the last 23 years (1995-2018) at our institution (n = 6900) was undertaken. This case illustrates a rare disease and highlights the importance of complete autopsy even in patients who might otherwise be signed out as an external exam or records review only.